2016
DOI: 10.1038/srep35559
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia endosymbionts induce neutrophil extracellular trap formation in human onchocerciasis

Abstract: The endosymbiotic bacteria, Wolbachia, induce neutrophilic responses to the human helminth pathogen Onchocerca volvulus. The formation of Neutrophil Extracellular Traps (NETs), has been implicated in anti-microbial defence, but has not been identified in human helminth infection. Here, we demonstrate NETs formation in human onchocerciasis. Extracellular NETs and neutrophils were visualised around O. volvulus in nodules excised from untreated patients but not in nodules from patients treated with the anti-Wolba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 44 publications
1
43
0
Order By: Relevance
“…NETs were recently demonstrated to be involved in the defense against incoming larvae of Strongyloides stercoralis 50. In human filarial nematode Onchocerca volvulus infections, NET formations were found around the adult worm containing nodules and the mechanism of NET formation was linked to the presence of Wolbachia and TLR2/651. The prominent role of neutrophils during the skin phase of L. sigmodontis infection in our study is in accordance with the study of Porthouse et al ., which showed that the very early immune response against incoming Brugia pahangi larvae is dominated by neutrophils and IL-652.…”
Section: Discussionsupporting
confidence: 92%
“…NETs were recently demonstrated to be involved in the defense against incoming larvae of Strongyloides stercoralis 50. In human filarial nematode Onchocerca volvulus infections, NET formations were found around the adult worm containing nodules and the mechanism of NET formation was linked to the presence of Wolbachia and TLR2/651. The prominent role of neutrophils during the skin phase of L. sigmodontis infection in our study is in accordance with the study of Porthouse et al ., which showed that the very early immune response against incoming Brugia pahangi larvae is dominated by neutrophils and IL-652.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, many filarial species harbor obligate bacterial endosymbionts ( Wolbachia ) which were recently shown to trigger NETosis ( 65 ). So far, it remains unclear whether microfilariae-triggered NETosis may interfere with antifilarial treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The onchocercomata (subcutaneous nodules) of patients contain worms positive for Wolbachia and exhibited high numbers of NETs. NETs were found in zones adjacent to the nematode cuticle, whereas nodules derived from patients treated with the anti-Wolbachia drugs, doxycycline + ivermectin were depleted for Wolbachia and lacked NETs 65 . More recently it was reported that NETs would drive inflammation in malaria by releasing soluble NET components to facilitate parasite sequestration and tissue destruction, and inhibition of NETs as a treatment strategy in vascular infections was recommended 16 .…”
Section: Nets In Viral Fungal and Parasitic Infectionsmentioning
confidence: 97%